Informativeness of ground penetrating radar method for investigations of the glaciers on Galindez, Winter and Skua Islands (the Argentine Islands, results for the period April to November 2017) - Chernov, A.P. (Український антарктичний журнал, 2017)
In this paper results of ground penetrating radar (GPR) surveying of island’s glaciers are shown. The main objectives were testing of VIY-3 300 GPR in weather conditions of Antarctica and check which information about glaciers can be obtained with this equipment.